18F‐FDG PET/CT as a predictor of hereditary head and neck paragangliomas. (March 2014) - Blanchet, Elise M.; Gabriel, Sophie; Martucci, Victoria; Fakhry, Nicolas; Chen, Clara C.; Deveze, Arnaud; Millo, Corina; Barlier, Anne; Pertuit, Morgane; Loundou, Anderson; Pacak, Karel; Taïeb, David
Abstract Background Hereditary head and neck paragangliomas (HNPGLs) account for at least 35% of all HNPGLs, most commonly due to germline mutations in SDHx susceptibility genes. Several studies about sympathetic paragangliomas have shown that 18F‐FDG PET/CT was not only able to detect and localize tumours, but also to characterize tumours (18F‐FDG uptake being linked to SDHx mutations). However, the data concerning 18F‐FDG uptake specifically in HNPGLs have not been addressed. The aim of this study was to evaluate the relationship between 18F‐FDG uptake and the SDHx mutation status in HNPGL patients. Methods 18F‐FDG PET/CT from sixty HNPGL patients were evaluated. For all lesions, we measured the maximum standardized uptake values (SUVmax), and the uptake ratio defined as HNPGL‐SUVmax over pulmonary artery trunk SUVmean (SUVratio). Tumour sizes were assessed on radiological studies. Results Sixty patients (53·3% with SDHx mutations) were evaluated for a total of 106 HNPGLs. HNPGLs‐SUVmax and SUVratio were highly dispersed (1·2–30·5 and 1·0–17·0, respectively). The HNPGL 18F‐FDG uptake was significantly higher in SDHx versus sporadic tumours on both univariate and multivariate analysis (P = 0·002). We developed two models for calculating the probability of a germline SDHx mutation. The first one, based on a per‐lesion analysis, had an accuracy of 75·5%. The second model, based on a per‐patient analysis, had an accuracy of 80·0%. Conclusions 18F‐FDG uptake in HNPGL is strongly dependent on patient genotype. Thus, the degree of 18F‐FDG uptake in these tumours can be used clinically to help identify patients in whom SDHx mutations should be suspected.